1996
DOI: 10.1507/endocrj.43.177
|View full text |Cite
|
Sign up to set email alerts
|

Short Term Treatment with Different Doses of Human Growth Hormone in Adult Patients with Growth Hormone Deficiency.

Abstract: Abstract.We studied the effects of short term replacement with human GH at three doses (0.124, 0.250 and 0.375 IU/kgBW/week) in 12 adult patients with GH deficiency (GHD). The patients were divided at random into three goups of 4 patients (groups A, B and C) and each group was treated with three doses of GH and placebo for 10 weeks in shifts of two weeks each. The replacement was started with one of three doses of GH given sc daily at 2100 h for 2 weeks, which was followed by placebo treatment for 2 weeks. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…With respect to anterior pituitary hormones, the administration of several doses of GH increased REM sleep in the rat 25 . In humans, GH deficiency syndrome is characterized by a reduction in sleep, and the administration of recombinant human GH generally helps to recover sleep; 26 however, in about 25% of patients, GH treatment induced sleep distress 27 . On the other hand, the administration of prolactin, 28 the induction of the release of endogenous prolactin, 29 and chronic hyperprolactinemia 30 are also associated with increased REM sleep.…”
Section: Effect Of Administration Of Pituitary Hormones On Sleepmentioning
confidence: 99%
“…With respect to anterior pituitary hormones, the administration of several doses of GH increased REM sleep in the rat 25 . In humans, GH deficiency syndrome is characterized by a reduction in sleep, and the administration of recombinant human GH generally helps to recover sleep; 26 however, in about 25% of patients, GH treatment induced sleep distress 27 . On the other hand, the administration of prolactin, 28 the induction of the release of endogenous prolactin, 29 and chronic hyperprolactinemia 30 are also associated with increased REM sleep.…”
Section: Effect Of Administration Of Pituitary Hormones On Sleepmentioning
confidence: 99%
“…Although most of the growth-promoting effects of GH are mediated through IGF-1, GH has biologic effects that occur independently of IGF-1. For example, GH enhances production of IGF-BP3 (32,33). In contrast, with IGF-1 therapy, GH secretion is inhibited, and IGF-BP3 production might decrease, which might decrease the half-life of IGF-1 (31).…”
Section: Discussionmentioning
confidence: 99%
“…In one study of 65 naive girls with Turner syndrome, who randomly received rhGH at 4 IU/m2 for 4 years, versus 4 IU/m2 for 1 year followed by 6 IU/m2 for 3 years, versus 4 IU/m2 for 1 year followed by 6 IU/m2 for 1 year and then 8 IU/m2 for 2 years, the area under the GH curve as well as the mean delta height SDS increased at the higher doses [37], GH-deficient adults, on the other hand, suffer a higher incidence of fluid retention when given doses adapted from childhood protocols, and experience a normaliza tion of IGF-I levels at much lower rhGH doses [38]. For example, 12 adults with GH-deficiency of childhood ori Optimizing Growth Hormone Therapy in Children gin were randomized to a 4-week crossover of daily rhGH at 0.125,0.25 and 0.50 IU/kg per week and obtained dosedependent rises in IGF-I and non-significant incremental elevations in IGFBP-3 and markers of bone metabolism [39], In another study of 12 adults with GH deficiency, a 2-week crossover of daily 0.124, 0.250 and 0.375 IU/kg per week rhGH also revealed a dose-dependent increase in IGF-I and IGFBP-3, but the highest dose was associat ed with more adverse effects [40]. Research evaluating dosing per body surface area found that dose-dependent elevations of IGF-I, IGFBP-3 and acid-labile subunit were obtained in the range of 0.33-3.0 IU/m2 per day.…”
Section: Gh Dosagementioning
confidence: 99%